Diseño de un plan de marketing para la empresa Tractoecuador Cía. Ltda., dedicada a la comercialización de repuestos para tractores y camiones, ubicada en el sector centro norte de la ciudad de Quito - Moncayo Pérez, Katherine Vanessa (2013)
Every company should implement a marketing plan, the same that achieves specific market objectives by controlling and creating strategies. To TRACTOECUADOR CIA. LTDA., We carried out an analysis of the macro environment and micro environment, with the same results the SWOT was applied at 7 P `s of marketing, where they found a number of strengths, weaknesses, opportunities and threats, identifying the level of impact of each component and the use of the respective matrices, we determined the needs of the company, the same to be remedied by the creation and implementation of strategies to improve the current situation and long term.